Body height, body mass index, waist-hip ratio, fluctuating asymmetry and second to fourth digit ratio in subjects with latent toxoplasmosis - Flegr, J; Hrusková, M; Hodný, Z; Novotná, M; Hanusová, J (Parasitology, 2005)
Between 20% and 60% of the population of most countries are infected with the protozoan Toxoplasma gondii. Subjects with clinically asymptomatic life-long latent toxoplasmosis differ from those who are Toxoplasma free in several behavioural parameters. Case-control studies cannot decide whether these differences already existed before infection or whether they were induced by the presence of Toxoplasma in the brain of infected hosts. Here we searched for such morphological differences between Toxoplasma-infected and Toxoplasma-free subjects that could be induced by the parasite (body weight, body height, body mass index, waist-hip ratio), or could rather correlate with their natural resistance to parasitic infection (fluctuating asymmetry, 2D : 4D ratio). We found Toxoplasma-infected men to be taller and Toxoplasma-infected men and women to have lower 2D : 4D ratios previously reported to be associated with higher pre-natal testosterone levels. The 2D : 4D ratio negatively correlated with the level of specific anti-Toxoplasma antibodies in Toxoplasma-free subjects. These results suggest that some of the observed differences between infected and non-infected subjects may have existed before infection and could be caused by the lower natural resistance to Toxoplasma infection in subjects with higher pre-natal testosterone levels.
Keywords: přirozená imunita; Male; poměr pasu a boků; Body Height; toxoplazmóza; mužské pohlaví; tělesná výška; Fingers; Immunity, Innate; Health Status; lidé; Toxoplasmosis; ženské pohlaví; prsty ruky; Humans; Body Mass Index; zdravotní stav; index tělesné hmotnosti; Female; Waist-Hip Ratio